EXPLORING MODERN METHODS IN COMPARATIVE LINGUISTICS - Ro’zabonu Abduqayumova; Zilola Abdurakhmanova Yoqubjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Comparative linguistics, a field tracing language evolution and relationships between different languages, has evolved significantly with the integration of modern methods and technologies. In recent years, scholars have embraced innovative approaches, including computational linguistics, evolutionary linguistics, and genetic linguistics, to delve deeper into the study of language origins, divergence, and connections.